2018
DOI: 10.1021/acs.jafc.7b04159
|View full text |Cite
|
Sign up to set email alerts
|

Novel Peptidase Kunitz Inhibitor from Platypodium elegans Seeds Is Active against Spodoptera frugiperda Larvae

Abstract: A novel Kunitz-type inhibitor from Platypodium elegans seeds (PeTI) was purified and characterized. The mass spectrometry analyses of PeTI indicated an intact mass of 19 701 Da and a partial sequence homologous to Kunitz inhibitors. PeTI was purified by ion exchange and affinity chromatographies. A complex with a 1:1 ratio was obtained only for bovine trypsin, showing a K = 0.16 nM. Stability studies showed that PeTI was stable over a wide range of temperature (37-80 °C) and pH (2-10). The inhibitory activity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(6 citation statements)
references
References 57 publications
2
4
0
Order By: Relevance
“…Primary metabolism genes such as 4-coumarate-CoA ligaselike 9 and sorbitol dehydrogenase-like were upregulated in H. armigera larvae exposed to SPIs (Table S1). This was consistent with previous work demonstrating that SPI ingestion impacts the regulation of genes involved in carbohydrate and lipid metabolisms in H. armigera, in addition to genes encoding digestive and detoxification enzymes [10,22]. A similar pattern was observed in the generalist herbivore L. migratoria [15].…”
Section: Discussionsupporting
confidence: 92%
“…Primary metabolism genes such as 4-coumarate-CoA ligaselike 9 and sorbitol dehydrogenase-like were upregulated in H. armigera larvae exposed to SPIs (Table S1). This was consistent with previous work demonstrating that SPI ingestion impacts the regulation of genes involved in carbohydrate and lipid metabolisms in H. armigera, in addition to genes encoding digestive and detoxification enzymes [10,22]. A similar pattern was observed in the generalist herbivore L. migratoria [15].…”
Section: Discussionsupporting
confidence: 92%
“…The noncompetitive mechanism found for the inhibition of ApTI on the trypsin‐like enzymes of A. gemmatalis agrees with other in silico studies carried out with trypsins from other species of the order Lepidoptera (Migliolo et al, 2010; Ramalho et al, 2018), and the reactive (inhibitory) peptide bond was identified in the alpha chain with the participation of the Arg64 residue and amino acid residues around Pro63, Ile65, and Arg66. This bond is at an exactly homologous position to the reactive sites identified in the soybean inhibitor at Arg‐63‐Ile‐64 (McPherson, Daym, & Larson, 2019) in Albizia at Arg‐66‐I1e‐67 (Sharma, Nath, Kumari, & Bhardwaj, 2012) and in Psophocarpus at Arg‐64‐Ser‐65 (Yamamoto, Hara, & Ikenaka, 1983).…”
Section: Discussionsupporting
confidence: 88%
“…The initial high affinity observed between IETI and trypsin was similar to that observed for the trypsin inhibitor from Entada scandens (Lingaraju and Gowda 2008) and followed the pattern observed for PIs with single reactive sites. The experimentally determined dissociation constant (Ki) was 6.2 nM, and the enzyme showed (Macedo et al 2007;Oliveira et al 2012;Ramalho et al 2018). The stability of IETI inhibitory activity was assayed over a range of temperatures, pHs and in the presence of the reducing agent, DTT.…”
Section: Resultsmentioning
confidence: 98%